2014
DOI: 10.1590/0100-2945-225/13
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da intensidade de poda na produção e qualidade de frutos de pessegueiro

Abstract: ). A interação 'Riograndense' e poda curta proporcionou maior percentual de frutos colhidos (91,02 %), maior massa média de frutos (141,62 g) e maior volume de massa fresca na poda de frutificação (3.188,14 g.planta -1 ), já a maior produtividade foi obtida em plantas de 'Riograndense', que receberam poda sem desponte (10,82 t.ha -1). Os diferentes tipos de poda influenciam no desenvolvimento das plantas, afetando o número de flores e frutos. Nas condições em que o experimento foi conduzido, podemos concluir q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…However, intense use of these pruning techniques may have drastic effects on plants, such as decreased yield in the year following the practice, leading to absent yield ("zero harvest"), and reduction in the root system, which in some cases may result in plant death due to the great removal of the vegetative part (Kumar et al, 2010;Gonçalves et al, 2014;Silva et al, 2016). Besides those problems, the use of traditional pruning in Arabica coffee culminates in disarray in the plant architecture, hindering cultivation practices such as harvesting as well as causing the "naked neck" effect.…”
Section: Introductionmentioning
confidence: 99%
“…However, intense use of these pruning techniques may have drastic effects on plants, such as decreased yield in the year following the practice, leading to absent yield ("zero harvest"), and reduction in the root system, which in some cases may result in plant death due to the great removal of the vegetative part (Kumar et al, 2010;Gonçalves et al, 2014;Silva et al, 2016). Besides those problems, the use of traditional pruning in Arabica coffee culminates in disarray in the plant architecture, hindering cultivation practices such as harvesting as well as causing the "naked neck" effect.…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al (2014) showed that high temperatures during the day and mild temperatures at night, especially during the maturation period, provide increased sugar content in peaches, which may favor mainly late cultivars harvested in December and January. According to Picolotto et al (2009) and Gonçalves et al (2014), the SS content of peaches are more influenced by some factors, such as position of the fruit in the plant, light interception into the canopy, branch and pruning type, than by the rootstock, and therefore may vary from one production cycle to another, being dependent on by 'Maciel'/'Industry', and 'Maciel'/'Capdeboscq', which did not differ between them (Figure 1). Finally, the results showed that the rootstocks evaluated induce distinct characteristics in the Maciel cultivar, such as differences in vigor, yield, and fruit quality (fruit size and sugar content in the pulp).…”
Section: Methodsmentioning
confidence: 99%
“…However, the peach produced in the southern region of Brazil, although of great flavor, often do not achieve the size, appearance and firmness desired by international standards (Wagner Junior et al, 2011;Gonçalves et al, 2014). Thus, orchard Com.…”
Section: Introductionmentioning
confidence: 99%
“…Sci., Bom Jesus, v.8, n.2, p.367-374, Abr./Jun. 2017 and plant management practices are important to reach these quality attributes (Gonçalves et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation